Respon beberapa galur mutan kedelai (Glycine max (L.) Merril) generasi M5 pada berbagai tingkat cekaman salinitas terhadap viabilitas dan vigor benih serta pertumbuhan vegetatif tanaman pada media Rockwool - Zuyasna Zuyasna; Ade Ryan Muarif; Hasanuddin Hasanuddin (Program Pascasarjana Universitas Papua, 2020)
This study aims to determine the effect of various levels of salinity on several M5 soybean mutant lines. This research was conducted at the Laboratory of Seed Science and Technology and the Screen House of the Agrotechnology Study Program, Faculty of Agriculture, Syiah Kuala University. The experiment design that used was factorial 5x4 with three replications and continued the analisis data with the Honest Real Difference Test (BNJ) at 5% level. The first factor was the soybean genotype with 5 levels, namely the Kipas Putih B4, B7 and B15 mutants, and Kipas Putih (mutant parent) and Wilis varieties were used as a comparison. The second factor is the concentration of NaCl which consists of 0 g L-1 (0 ds / m), 4 g L-1 (4 ds / m), 6 g L-1 (5 ds / m), and 8 g L-1. (5.5 ds / m). The results showed that each genotype had different resistance to salinity. At a concentration of NaCl 4 gL-1 (4 ds / m), the genotype has begun to show a decrease in the value of viability and vigor of seeds as well as plant vegetative growth. There is no soybean genotype that is tolerant to salinity with the ability to germinate and grow above 80% or more. The genotypes of Wilis, Kipas Putih and mutants B4 had relatively better germination and growth power in salinity stress compared to mutants B7 and B15.